Beberapa Sifat Fisik dan Infiltrasi Tanah Setelah Revegetasi pada Lahan Pasca Penambangan Batubara: The Several of Physical Properties and Soil Infiltration After Revegetation of Post Coal Mining Land - Endriani, Endriani; Fuadi, Najla Anwar; Wahyudi, Rizki (Fakultas Kehutanan Universitas Jambi, 2026)
ABSTRACT This study aims to examine the impact of revegetation on post-coal mining land on soil physical properties and infiltration. The research was carried out in the reclamation post coal mining land PT. Nan Riang, Muara Tembesi District, Batanghari Regency, Jambi Province, on inactive disposal land, sengon 4 years old, jabon 7 years old, and rambutan 9 years old. This study uses the survey method and the selection of representative areas using the Purposive Random Sampling method. infiltration measurements were carried out using a double ring infiltrometer on each revegetation with three time. Revegetation post coal mining land showed an improvement in soil physical properties and soil infiltration compared to inactive disposal. The top soil layer (0-30 cm) on revegetation land with jabon and rambutan increased soil organic matter (4.84% and 4.75%) followed by sengon (3.67 %) compared to inactive disposal land (1.59%), decreased the weight of the volume of jabon and rambutan revegetation (1.01 g/cm3 and 1.20 g/cm3) followed by sengon (1.27 g/cm3) compared to inactive disposal (1.73 g/cm3), increasing the total soil pore space in jabon revegetation, Rambutan, and Sengon (62.01%; 54.72%; 52.08%) compared to inactive disposal (34.72%), increased soil permeability in the revegetation of Jabon, Rambutan, Sengon (20.65 cm/hour; 19.09 cm/hour; 10.10 cm/hour) compared to inactive disposal (1.66 cm/hour). The infiltration rate and infiltration capacity increased after revegetation with jabon (4.01 cm/h and 18.09 cm/h), rambutan (2.96 cm/h and 15.47 cm/h), sengon (2.21 cm/h and 11.98 cm/h), inactive disposal (1.69 cm/h and 5.96 cm/h). Keywords: infiltration, post coal mining, revegetation, soil physical properties ABSTRAK Penelitian ini bertujuan untuk mengkaji dampak revegetasi pada lahan pasca tambang batubara terhadap sifat fisika tanah dan infiltrasi. Penelitian dilakukan di areal reklamasi lahan pasca tambang batubara PT. Nan Riang Kecamatan Muara Tembesi Kabupaten Batanghari Provinsi Jambi, pada lahan disposal tidak aktif, sengon umur 4 tahun, jabon umur7 tahun, dan rambutan umur 9 tahun. Penelitian ini menggunakan metode survey dan pemilihan areal pewakil dengan menggunakan metode Purposive Random Sampling. Pengukuran infiltrasi dilakukan menggunakan double ring infiltrometer. Revegetasi lahan pasca penambangan batubara menunjukkan terjadi perbaikan sifat fisik tanah dan infiltrasi tanah dibandingkan disposal tidak aktif. Lapisan tanah atas (0-30 cm) pada lahan revegetasi dengan jabon dan rambutan meningkatkan bahan organik tanah (4,84 % dan 4,75%) diikuti revegetasi sengon (3,67%) dibandingkan lahan disposal tidak aktif (1,59%), menurunkan bobot volume revegetasi jabon dan rambutan (1,01 g/cm3 dan 1,20 g/cm3) diikuti sengon (1,27 g/cm3) dibandingkan disposal tidak aktif (1,73 g/cm3), meningkatkan total ruang pori tanah pada revegetasi jabon, rambutan, dan sengon (62,01%; 54,72%; 52,08%) dibandingkan disposal tidak aktif (34,72%), meningkatkan permeabilitas tanah pada revegetasi jabon, rambutan, sengon (20,65 cm/jam; 19,09 cm/jam; 10,10 cm/jam) dibandingkan dengan disposal tidak aktif (1,66 cm/jam). Laju infiltrasi dan kapasitas infiltrasi meningkat setelah revegetasi dengan jabon (4,01cm/jam dan 18,09 cm/jam), rambutan (2,96 cm/jam dan 15,47 cm/jam), sengon (2,21 cm/jam dan 11,98 cm/jam), disposal tidak aktif (1,69 cm/jam dan 5,96 cm/jam). Kata kunci: iInfiltrasi, pasca tambang batubara, revegetasi, sifat fisik tanah